Peran Budaya Organisasi Hijau dalam Membentuk Perilaku Ramah Lingkungan Aparatur Sipil Negara - Ifa Masluhah; Moh. Khusaini; Bunga Hidayati (Jurnal Ilmiah Pendidikan Pancasila dan Kewarganegaraan, 2026)
This study aimed to analyze the influence of environmental leadership and environmental awareness on the pro-environmental behavior of civil servants in Malang City, while examining the role of green organizational culture within this relationship. A quantitative approach was employed using a survey method witth a cross-sectional design involving civil servants in the Malang City Government. Data were collected through a Likert-scale questionnaire administered to 136 respondents and were analyzed using Structural Equation Modeling–Partial Least Squares. The results indicated that environmental awareness had a positive and significant effect on pro-environmental behavior and was identified as the dominant factor in explaining behavioral variation. In contrast, environmental leadership did not show a significant effect. Green organizational culture was not found to strengthen the relationship between environmental leadership and environmental awareness with pro-environmental behavior. These findings suggested that pro-environmental behavior among civil servants was more influenced by internal individual factors than by structural organizational factors.